Isolation and structure determination of a new analog of polycavernosides from marine Okeania sp. cyanobacterium - Umeda, Kairi; Kurisawa, Naoaki; Jeelani, Ghulam; Nozaki, Tomoyoshi; Suenaga, Kiyotake; Iwasaki, Arihiro (Beilstein Journal of Organic Chemistry, 2024)
Polycavernoside E (1), a new polycavernoside analog, was isolated from a marine Okeania sp. cyanobacterium. The relative configuration was elucidated primarily by analyzing the two dimensional nuclear magnetism resonance (2D NMR) data. The absolute configuration was clarified by comparing the electronic circular dichroism (ECD) data of 1 with those of known analogs. Polycavernoside E (1) exhibited moderate antitrypanosomal activity against Trypanosoma brucei rhodesiense. Furthermore, the isolation of polycavernoside E (1) from marine cyanobacteria provides additional evidence that marine cyanobacteria, and not red algae, are responsible for the biosynthesis of polycavernosides.
Keywords: macrolide glycoside; marine cyanobacterium; marine natural products; polycavernosides; terminal alkyne